Development of the Diabetes Technology Society Blood Glucose Monitor System Surveillance Protocol. (May 2016) - Klonoff, David C.; Lias, Courtney; Beck, Stayce; Parkes, Joan Lee; Kovatchev, Boris; Vigersky, Robert A.; Arreaza-Rubin, Guillermo; Burk, Robert D.; Kowalski, Aaron; Little, Randie; Nichols, James; Petersen, Matt; et al.
Background: Inaccurate blood glucsoe monitoring systems (BGMSs) can lead to adverse health effects. The Diabetes Technology Society (DTS) Surveillance Program for cleared BGMSs is intended to protect people with diabetes from inaccurate, unreliable BGMS products that are currently on the market in the United States. The Surveillance Program will provide an independent assessment of the analytical performance of cleared BGMSs. Methods: The DTS BGMS Surveillance Program Steering Committee included experts in glucose monitoring, surveillance testing, and regulatory science. Over one year, the committee engaged in meetings and teleconferences aiming to describe how to conduct BGMS surveillance studies in a scientifically sound manner that is in compliance with good clinical practice and all relevant regulations. Results: A clinical surveillance protocol was created that contains performance targets and analytical accuracy-testing studies with marketed BGMS products conducted by qualified clinical and laboratory sites. This protocol entitled "Protocol for the Diabetes Technology Society Blood Glucose Monitor System Surveillance Program" is attached as supplementary material. Conclusion: This program is needed because currently once a BGMS product has been cleared for use by the FDA, no systematic postmarket Surveillance Program exists that can monitor analytical performance and detect potential problems. This protocol will allow identification of inaccurate and unreliable BGMSs currently available on the US market. The DTS Surveillance Program will provide BGMS manufacturers a benchmark to understand the postmarket analytical performance of their products. Furthermore, patients, health care professionals, payers, and regulatory agencies will be able to use the results of the study to make informed decisions to, respectively, select, prescribe, finance, and regulate BGMSs on the market.